2013
DOI: 10.1111/jcmm.12042
|View full text |Cite
|
Sign up to set email alerts
|

Changes of lysosomes in the earliest stages of the development of atherosclerosis

Abstract: One of hypotheses of atherosclerosis is based on a presumption that the zones prone to the development of atherosclerosis contain lysosomes which are characterized by enzyme deficiency and thus, are unable to dispose of lipoproteins. The present study was undertaken to investigate the characteristics and changes of lysosomes in the earliest stages of the development of atherosclerosis. Electron microscopic immunocytochemistry revealed that there were certain changes in the distribution of CD68 antigen in lysos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Experiments utilizing macrophages in in vitro experiments demonstrated that modified low density lipoproteins (LDL) are captured by macrophages followed by association of vacuoles containing LDL with lysosomes ( Fig. 2A) [10,11]. The molecular mechanisms of interaction of modified LDL with macrophages have been detailed in a large number of reviews [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Experiments utilizing macrophages in in vitro experiments demonstrated that modified low density lipoproteins (LDL) are captured by macrophages followed by association of vacuoles containing LDL with lysosomes ( Fig. 2A) [10,11]. The molecular mechanisms of interaction of modified LDL with macrophages have been detailed in a large number of reviews [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 98%
“…The functional insufficiency of lysosomes is thought to lead to excessive accumulation of lipids ("lipid droplets") in the cytoplasm of macrophages (Fig. 3A, B) [10,18,19]. Eventually, macrophages engulfing modified LDL become overloaded with lipids, and this transforms them into foam cells (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…57 Ultrastructural studies of human atherosclerotic lesions demonstrated that CD68 is mostly located in lysosomes (Figure 3). 58,59 In contrast to macrophages, 59 CD68 is not expressed by dendritic cells (DCs) 14,60 and this helps to immunohistochemically distinguish these two cell types, both of which have antigenpresenting capabilities. Several studies have shown significant upregulation of CD68 expression in macrophages in response to inflammatory stimuli such as exposure to oxLDL 12,49,50 and chronic stimulation with bacterial lipopolysaccharide (LPS) or inflammatory cytokine interferon-γ (IFN-γ).…”
Section: Cd68: a Role In Inflammation And Immunitymentioning
confidence: 99%
“…In human aortic tissues, lysosomal change has been confirmed in the early stage of atherosclerosis [29]. Lysosomal hyrolases and proteins have been involved in lipid and cholesterol metabolisms [30].…”
Section: Discussionmentioning
confidence: 99%